Reliability study on the half-cutting PERC solar cell and module - Sungho Hwang; Yoonmook Kang (Energy Reports, 2023)
In the photovoltaic industry, there are three critical parameters such as module power, cost and reliability. For increasing module power, half-cutting technology on the cell is one of the technologies because this can reduce the heating power by reducing the current. Therefore, laser scribing and mechanical cleaving (LSMC) technology have been implemented. As a result, the power of the module did not show any loss during standard test conditions when electrical luminescence and powers were monitored for the laser dicing process. However, in field conditions, the cut side of the cells with the laser process can cause cell breakage by wind or snow if the side has cracks. And then these crack cells can finally cause module power loss. Therefore, in this study, the laser process quality of the cell has been investigated by microscope image and scanning electron microscopy with laser process parameters such as laser power, frequency, and pulse width. In addition, cell strength was also checked by the four points of bending force to find the optimized laser process condition. The module power loss was analyzed with a static mechanical load test (MLT), which can represent snow or wind effect in the field. Our analyses show a strong correlation between crack width by laser, cell bending force, and module power loss. This correlation can explain the module power loss estimation, which can affect the reliability in the field without making module-level tests for the first time. In addition, the encapsulant thickness combination test and the mid-rail effect were also presented to reduce the power loss. As a result, the module power loss reached -1.34%. Finally, this study can contribute to the better reliability of the big wafer size products with LSMC technology.